Biopotential of rhizobacteria to improve growth and phytochemical content in Javanese ginseng (Talinum paniculatum) herbal plant - Suriani, Ni Luh; Suprapta, Dewa Ngurah; Suarsana, I. Nyoman; Resiani, Ni Made Delly; Perveen, Kahkashan; Bukhari, Najat A.; Ei Enshasy, Hesham Ali; Ho, Ting Seng; Sayyed, R. Z. (Frontiers in Sustainable Food Systems, 2024)
Introduction Developing organic herbal crops provides chemical-free herbs to support environmentally friendly and sustainable farming. One way in agricultural biotechnology to grow herbal organic crops is to use rhizobacteria. The herbal plant used in this study is the Javanese ginseng plant (Talinum paniculatum), which contains phytochemicals that increase stamina. Methods The study used four rhizobacteria to enhance the growth and phytochemistry of T. paniculatum leaves; the target phytochemical compounds analyzed in Javanese ginseng leaves were total flavonoids, total phenols, and antioxidants (IC50%). The four selected rhizobacteria can produce indole-3-acetic acid (IAA), fix nitrogen, and dissolve phosphate. Thus, high-quality T. paniculatum leaves were obtained as herbal tea ingredients. The pattern used is a random group pattern in the greenhouse. Results The results of the study showed that the use of rhizobacteria at 2% concentrations had a real effect on plant growth parameters such as plant height, leaf area, root length, wet weight and dry weight of the plant, and phytochemical content like total flavonoids, total phenols, IC50%, total chlorophyll, content of T. paniculatum leave plant when compared to the control. The four rhizobacteria used can produce the IAA, fix nitrogen, and dissolve phosphorus. Discussion The four rhizobacteria can also colonize the root of the T. paniculatum plant. The four Rhizobzcteria used significantly affected the growth and phytochemical content of T. paniculatum leaves as an ingredient in herbal tea at a concentration of 2% compared to controls. The four rhizobacteria can produce IAA hormones, fix nitrogen, and dissolve phosphorus. All four rhizobacteria can colonize the roots of T. paniculatum plants. These four rhizobacteria can be used as alternative methods in developing organic farming systems and can also be used practically in the field by farmers. It is necessary to research the application of rhizobacteria to other crops to support sustainable agriculture.